Brain on the stage - Spotlight on nervous system development in zebrafish: EMBO practical course, KIT, Sept. 2013 - Scholpp, Steffen; Poggi, Lucia; Žigman, Mihaela (Neural development, 2013)
During the EMBO course ‘Imaging of Neural Development in Zebrafish’, held on September 9-15th 2013, researchers from different backgrounds shared their latest results, ideas and practical expertise on zebrafish as a model to address open questions regarding nervous system development.
Gesehen am 17.05.2017